The Great Depression and the Decline of Liberal Capitalism: Polanyi and Schumpeter - Trigilia, Carlo (Economic Sociology, 2002)
This chapter contains section titled: * Market Domination and Society's Self-Defense * The Decline of the Bourgeoisie and Anti-Capitalist Policies * Analytical Convergence and Political Divergence
Keywords: SCHUMPETER, Joseph Alois, 1883-1950; capitalism; depression; economic level; economic sociology; international relations; social conditions